Views of Orientalists on Shariat and customs - Amirov A.M., А. М. (Journal of Oriental Studies, 2024)
The article provides information about the gradual appearance of a variety of stereotypes and negative beliefs of Western society concerning the “East”, also most researchers of life, traditions and the Kazakh lands, who were adhering to the Muslim religion during the Imperial Russia, were Russian population. Researchers claim who said that the Kazakh people are not Muslims, were in many cases the followers of Imperial Russian policy. Actuality lies in the objective views of orientalists about the life and traditions of Edward Saidt, academic V.V. Bartold and Kazakh scientist Ualihanov Ch.Ch. and others that was taken as a framework